2016
DOI: 10.1108/jima-07-2014-0050
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting patronage factors of Islamic credit card as a new e-commerce banking service

Abstract: Purpose Understanding the important patronage factors of Islamic credit card as a new e-commerce banking service is essential for bankers and users. Although some previous studies have focused on the factors that influence adoption of Islamic credit card, there are few empirical research studies that use a well-established adoption model that helps bankers and consumers to accept and use the Islamic credit card. This study aims to provide such a model to facilitate the adoption of Islamic credit card. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 81 publications
(95 reference statements)
12
84
3
4
Order By: Relevance
“…Therefore, H5 is supported. (Jamshidi et al, 2016;Jaffar et al, 2015;Alam, 2013;Hassan et al, 2013;Butt et al, 2011;Sun et al, 2012;Sufian, 2007). Jaffar et al (2015) revealed that 'Religion obligation is the influencing factor of attitude, which coincides with Butt et al (2011) study'.…”
Section: Empirical Results and Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Therefore, H5 is supported. (Jamshidi et al, 2016;Jaffar et al, 2015;Alam, 2013;Hassan et al, 2013;Butt et al, 2011;Sun et al, 2012;Sufian, 2007). Jaffar et al (2015) revealed that 'Religion obligation is the influencing factor of attitude, which coincides with Butt et al (2011) study'.…”
Section: Empirical Results and Discussionmentioning
confidence: 58%
“…Islamic Religious Promotion and IB: Religious promotion is a major determinant of IB adoption (Jamshidi et al, 2016;Jaffar et al, 2015;Alam, 2013;Hassan et al, 2013;Butt et al, 2011;Sun et al, 2012;Sufian, 2007). In Malaysia, Muhamat et al (2008) the measured of the sensitivity of the banks' customers towards the use of Arabic terminology in the Islamic banking industry.…”
Section: Determinants Of Islamic Banking Adoption Across Different Rementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that proved that perceived ease of use or perceived usefulness influenced attitude toward behavior were conducted by Scanell et al (2011), Huang et al (2015, and Miranda et al (2017). The studies by Lin (2011), Hsiao and Tang (2013) and Jamshidi and Hussin (2016), Ye and Zhang (2014) proved not only the influence of perceived ease of use or perceived usefulness on attitude toward behavior but also the influence of perceived ease of use on the perceived usefulness.…”
Section: H1: Perceived Ease Of Use (Peu) Affects Perceived Usefulnessmentioning
confidence: 97%
“…Previous studies on e-commerce topics were generally more towards online buyers (Iqbal et al 2012;Shalini andHemamalini 2015, andDachyar andBanjarnahor 2017) or the adoption of e-commerce in MSMEs (Savrul et al 2014, Rahayu and John Day 2015, Venkatesh and Kumari 2015and Ueasangkomsate 2015. Studies on e-commerce topics related to intention theory generally applied TAM (Lesmono 2015, Jamshidi and Hussin 2016, Dachyar and Banjarnahor 2017and Natarajan et al 2017 whereas the study of credit applying intention theory usually applied TPB (Abdullah and Wahab 2015, Makpotche et al 2015, Brizi et al 2016, Kajenthiran et al2016and Tolba et al 2016).…”
Section: Introductionmentioning
confidence: 99%